2023
DOI: 10.3390/nu15184067
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Inflammatory Index and Risk of Colorectal Adenomatous Polyps in Kashgar Prefecture of Xinjiang, China

Zhuo-Jie He,
Weili Yusufu,
Shuang Zhang
et al.

Abstract: Malignant colorectal tumors and precancerous lesions are closely associated with chronic inflammation. Specific dietary patterns can increase chronic inflammation in the body, thereby promoting the occurrence of tumors and precancerous lesions. We have conducted a case–control study in Kashgar Prefecture, Xinjiang, China, to explore the association between the energy-adjusted dietary inflammatory index (E-DII) and the risk of colorectal adenomatous polyps (CAP). A total of 52 newly diagnosed patients with CAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The effect of probiotics was more clearly demonstrated in experiments in mouse models, where it was shown that 14 probiotic strains isolated from fermented camel milk had positive effects on blood glucose and lipids, delaying the development of T2DM and stimulating the secretion of GLP-1 [100]. In addition, 4 of these 14 probiotic strains of microorganisms were found to alleviate cyclophosphamide-induced immunodeficiency in mice and exert antitumor effects by regulating the CD4+/CD8+ cell ratio and increasing the secretion of Th1-type cytokines [101]. In addition to probiotics, bioactive peptides isolated from shubat from Xinjiang were found to have anti-inflammatory and immunomodulatory functions, as well as stimulating effects on mouse splenic lymphocyte proliferation and the expression of IFN-γ in lymphocytes [102].…”
Section: Probiotic Properties Of Shubatmentioning
confidence: 98%
“…The effect of probiotics was more clearly demonstrated in experiments in mouse models, where it was shown that 14 probiotic strains isolated from fermented camel milk had positive effects on blood glucose and lipids, delaying the development of T2DM and stimulating the secretion of GLP-1 [100]. In addition, 4 of these 14 probiotic strains of microorganisms were found to alleviate cyclophosphamide-induced immunodeficiency in mice and exert antitumor effects by regulating the CD4+/CD8+ cell ratio and increasing the secretion of Th1-type cytokines [101]. In addition to probiotics, bioactive peptides isolated from shubat from Xinjiang were found to have anti-inflammatory and immunomodulatory functions, as well as stimulating effects on mouse splenic lymphocyte proliferation and the expression of IFN-γ in lymphocytes [102].…”
Section: Probiotic Properties Of Shubatmentioning
confidence: 98%
“…These types of food exhibit low nutritional quality, a high glycaemic load, and insufficient fibre and micronutrients, predisposing people to an increased risk of CRC. In addition, there is an association between colorectal tumours and chronic inflammation [2,4,6,[8][9][10]. Specific diet patterns can increase chronic inflammation by altering the microbiota of the body, thereby promoting the onset of tumours and precancerous lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a state of chronic low inflammation, which some authors call "meta-inflammation", that is, a state of chronic metabolic inflammation, which is behind many of today's chronic diseases. To this, we must add data showing the epigenetic changes induced by metabolites of the microbiota that could be transmitted to the next generation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations